CHRONIC DISEASES IN CHILDREN AND ADOLESCENTS - SOME PSYCHOLOGICAL CHARACTERISTICS - Pop-Jordanova N; Fustic, S; Zorcec, T (My University, 2008)
A significant number of children suffer from chronic diseases, which demand careful adjustment, and the coping and active role of all involved in the treatment. Psychological problems in this population are increased by the long duration of procedures, specific diet and low physical activity. In this study various psychometric instruments are used to evaluate the psychological characteristics of children and adolescents suffering from cystic fibrosis, juvenile rheumatoid arthritis, diabetes mellitus and cancer. The obtained results are compared between groups as well as with a control. Children with cystic fibrosis and neuroticism appeared to be more aggressive, while those with juvenile rheumatoid arthritis and cancer more anxious and depressed in comparison with the control. The personality profiles in adolescents with cystic fibrosis and cancer is similar, showing Hs-D-Hy peaks. Manifest depression is found only in the group with cancer and occasionally in cystic fibrosis. The profiles for diabetics showed emotional instability as well as some psychopathological traits. Generally, psychological functioning in all children is not so impaired. Multidisciplinary teamwork is needed to overcome the psychological problems that occur as well as to ensure good quality of life.
Keywords: CHRONIC DISEASE - psychology; ADAPTATION , PSYCHOLOGICAL; CHILD PSYCHOLOGY